THERAPEUTIC EFFECTS OF HYDRO-ETHANOLIC EXTRACT OF Nigella sativa (BLACK SEED) ON SOME HAEMATOLOGICAL PARAMETERS OF ALBINO RATS AFTER LEAD EXPOSURE - Abubakar A; Tukur MA; Ibrahim BM; Isa BI; Salami HA (Ntec Specialist, 2020)
Background: Lead poisoning is a great public health concern in Africa and Nigeria, especially regions where illegal mining activities occur such as widespread gold ore mining in Zamfara by artisan miners using rudimentary and unsafe processing techniques. Lead (Pb) which often have no biological function remain in the system causes havoc and distortion of normal physiologic functions. Currently, the toxic effects of lead poisoning are clinically treated using chelation therapy which have been associated with many side effects and setbacks. Since ancient times, medicinal plants have been used as a major source of treatment for numerous human diseases. Plants that possess hematinic and antioxidant properties in the plant kingdom are often used in such scenarios. One of such plants is Nigella sativa commonly known as black cumin. Objectives: In this study, therapeutic effects of hydroethanolic extracts of Nigella sativa was assessed on hematological parameters of lead- poisoned albino rats as a curative therapy for management of lead poisoning. Method: Thirty- five (35) adult albino wistar rats of both sexes were used for this study. Group I (Normal control) received 2ml/kg of distilled water, Group II (Negative control), Group III treated with 10 mg/kg of Meso-2,3 Dimercaptosuccinic acid (DMSA), Group IV treated with 200 mg/kg of Nigella sativa seed extract, Group V treated with 400 mg/kg of Nigella sativa seed extract, and Group VI treated with 800mg/kg of Nigella sativa seed extract for Group VII (Recovery) were allowed to recover without treatment. The study lasted for a duration of 21days. Blood samples were collected from the rats through cardiac puncture after anesthetizing the animals and analysed for haematological parameters which included RBC count, PCV, Hb concentration, platelet count, WBC profile and haematological indices using an automated digital blood analyser. Results: Nigella sativa seed extract significantly (P less than 0.05) reversed the adverse effect of Lead exposure on RBC count, PCV, Hb concentration, platelet count, WBC profile and haematological indices. Conclusion: Nigella sativa showed therapeutic effects on haematological parameters and indices of lead poisoned albino rats.